Creating the illusion backstage at the Met - Metropolitan Opera Guild. Education Department (New York : The Metropolitan Opera Guild, 1986)
Takes you behind the scenes to see how the dozens of artisans and technicians work together to transform the vast Met stage into a world of fantasy.
Script, Sarah Lang.
Naomi Robin and Michael Bevine.
Keywords: Opera -- Production and direction